Dizziness in community-dewelling older adults: a population-based study - Moraes, Suzana Albuquerque de (2011)
Dizziness is a common complaint among older adults.Aim: To identify the prevalence of dizziness and its related factors in a sample of community-dwelling older adults.Methods: A prospective population-based study with a representative sample of older adults aged 65 years and over. A multidimensional questionnaire and a battery of measures were used for assessing physical function.Results: The prevalence of dizziness was 45%. Vertigo was found in 70.4% of older adults with dizziness and 43.8% of them referred vertigo crises along life. A significant association was found between dizziness and female gender (p=0.004), memory difficulties complaints (p=0.015), bad health perception (p=0.001), depression (p<0.0001), five or more comorbidities (p=0.021), self-reported fatigue (p<0.0001), recurrent falls (p=0.001), excessive sleepiness (p=0.003), fear of falling (p<0.0001), left leg unipedal stance (p=0.002) and Short Performance Physical Battery score (p=0.009).Conclusion: Dizziness is a common complaint among older adults and it is associated with limiting clinical conditions, such as depression, fatigue, excessive sleepiness and impaired memory. It is highlighted the association between dizziness and recurrent falls, fear of falling and lower performance in physical function tests, which can restrict independence. These data suggest the importance of a multifactorial approach to dizziness in older adults.